Potential Therapeutic Implications of Caffeic Acid in Cancer Signaling: Past, Present, and Future - Alam, Manzar; Ashraf, Ghulam Md; Sheikh, Kayenat; Khan, Anish; Ali, Sabeeha; Ansari, Md. Meraj; Adnan, Mohd; Pasupuleti, Visweswara Rao; Hassan, Md. Imtaiyaz (Frontiers in Pharmacology, 2022)
Caffeic acid (CA) is a bioactive compound found in many plants, including vegetables, herbs, fruits, and drinks. CA exhibits various health advantages linked with its anti-oxidant functions and is implicated in the prevention and treatment of cancer and inflammatory diseases. The anti-tumor action of CA is associated with its anti-oxidant and pro-oxidant capability. CA may act via preventing ROS formation, stimulating the DNA oxidation of tumor cells, decreasing cancer cell angiogenesis, and repression of matrix metalloproteinase (MMP)-2 & -9. CA represses the action of MMP-9 enzyme and transcriptional decrease-regulation through the dual blockage of NF-κB and MMP-9 catalytic action. CA and its derivatives exhibited anti-carcinogenic action against numerous types of cancers. CA has indicated low intestinal absorption, low oral bioavailability in rats, and pitiable permeability across Caco-2 cells. A brief overview of the literature published on the therapeutics properties of CA and the future perspectives of research on CA have been described. This review aimed to illustrate CA's characteristics, pharmacokinetics, and therapeutic potential. The pharmacological effects of CA, the emphasis on in vitro and in vivo studies, and the existing challenges and prospects of CA for cancer treatment and prevention.